치과위생사의 코로나19 감염관련 지식, 감염관리 수행 및 사회심리적 건강 관련 연구 - 문상은; Sang-eun Moon; 양진주; Jin-ju Yang; 홍선화; Sun-Hwa Hong; 이보람; Bo-ram Lee; 김희정; Hui-jeong Kim; 서가혜; Ga-hye Seo; et al. (Han'guk Ch'iwisaeng Hakhoe chi, 2021)
Objectives: This study aimed to verify the relations of COVID-19 infection-related knowledge, dental infection control performance, and psychosocial health of dental hygienists. Methods: From the data was analyzed through the frequency analysis, t-test, one way ANOVA, and pearson’s correlation analysis with a total of 198 dental hygienists using SPSS Statistics 21.0. Results: The correct answer rate for knowledge about COVID-19 was higher with a bachelor’s degree or higher. Thus, when the level of education was higher, the performance was also high (p<0.01). COVID-19 infection control performance was highly shown in case of high age (4.43) (p<0.05) and the married (4.42) (p<0.01). Infection control performance was high when they had an educational experience of COVID-19 infection control (4.46), and when the infection control guidebooks were equipped in their workplaces (p<0.001). Degree of psychosocial health of research subjects was shown in the order of potential stress (60.6%), high-risk stress (23.7%), and healthy (15.7%). Infection control performance was higher, the psychosocial health was healthy. Conclusions: For the response to COVID-19 infectious disease and the preparation for mutated viruses and new infectious diseases in the future, it would be necessary to establish the concrete measures for establishing the strict infection control system for dental clinics and also enhancing the psychosocial health of dental hygienists.